Assessment of Heavy Metals Pollution in Marine Surface Sediments of Gaza Strip, Southeast the Mediterranean Sea - Ubeid, Khalid Fathi; Al-Agha, Mohammad; Almeshal, Wael (Journal of Mediterranean Earth Sciences, 2018)
The current study investigates the grain-size distribution of the sediments in two surveys along coastal line of the Gaza Strip, at the tide and shelf zones. The concentrations of Zn, Pb, Mn, Cu, Co, and Cd in the surface sediments of the study area were evaluated from thirty location sites selected in the two zones. The grain size-distribution of the sands in tide zone along the study area shows that the predominant grain-size was medium- to fine-grained, while the predominant grain-size in the shelf was fine- to very fine-grained. For the heavy metal concentrations, the results show that the mean concentration values in the shelf along the study area are higher than those in tide zone, except the Pb. The mean concentrations of heavy metals in the tide zone of Zn, Pb, Mn, Cu, Co, and Cd are 11.56, 15.86, 20.49, 1.72, 3.24, and 0.90 mg/kg respectively, while the concentrations in the shelf are 14.92, 14.07, 198.07, 2.00, 4.51, and 1.30 mg/kg, respectively. Generally, the results suggest that the heavy metal levels increase with decreasing the average grain-size of the sediments in the study area. The beach of Gaza Strip is considered as one of the most polluted areas due to the adverse effect of effluents from land-based sources. Domestic untreated wastewater discharges and fishing activities in the harbors area may possibly the major source of the observed higher levels of heavy metals contamination, especially the cadmium and lead. However, the concentration levels of the studied heavy metals in the study area are under the limits comparing with EPA and Ontario guideline standards, except the Cd level is mainly above the limits of EPA and Ontario.